Mechanism of spin crossover in LaCoO3 resolved by shape magnetostriction in pulsed magnetic fields - Rotter, M; Wang, Z; Boothroyd, A; Prabhakaran, D; Tanaka, A; Doerr, M (Springer Nature, 2014)
In the scientific description of unconventional transport properties of oxides (spin-dependent transport, superconductivity etc.), the spin-state degree of freedom plays a fundamental role. Because of this, temperature- or magnetic field-induced spin-state transitions are in the focus of solid-state physics. Cobaltites, e.g. LaCoO3, are prominent examples showing these spin transitions. However, the microscopic nature of the spontaneous spin crossover in LaCoO3 is still controversial. Here we report magnetostriction measurements on LaCoO3 in magnetic fields up to 70 T to study the sharp, field-induced transition at Hc ≈ 60 T. Measurements of both longitudinal and transversal magnetostriction allow us to separate magnetovolume and magnetodistortive changes. We find a large increase in volume, but only a very small increase in tetragonal distortion at Hc. The results, supported by electronic energy calculations by the configuration interaction cluster method, provide compelling evidence that above Hc LaCoO3 adopts a correlated low spin/high spin state.